2012
DOI: 10.1002/pc.22350
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties and microstructures of cellulose acetate phthalate/hydroxypropyl cellulose blends

Abstract: Cellulose acetate phthalate (CAP)/hydroxypropyl cellulose (HPC) blends were investigated by means of attenuated total reflection‐Fourier transform infrared spectroscopy, thermogravimetry/differential thermal analysis, shear viscosity, oscillatory shear tests, and atomic force microscopy (AFM). Effect of solution concentrations in 2‐methoxyethanol, blend compositions, and shear rate on the rheological functions reflects the mobility of the chain segments or their orientation—with thinning behavior in the shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Interpretation of surface properties results must be performed starting from CAP 36 The occurrence of hydrogen bond structures in blends can be evidenced from peaks shape and intensity of the absorption band of the hydrogen stretching vibration. 23 The differences observed among the shape, broadening, and shifting of the mentioned peaks for polymer blends suggest the existence of hydrogen bonding, generated by AOH, C@O, and CAOAC groups. The free and associated groups provide the equilibrium in these polymer blends via hydrogen bonds; (b) Quantitative measurements of weight loss from TG/DTG plots show that CAP is less thermally stable than the HPC and CAP/HPC blends, as the anhydroglucose units increase the rigidity of the HPC chain.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Interpretation of surface properties results must be performed starting from CAP 36 The occurrence of hydrogen bond structures in blends can be evidenced from peaks shape and intensity of the absorption band of the hydrogen stretching vibration. 23 The differences observed among the shape, broadening, and shifting of the mentioned peaks for polymer blends suggest the existence of hydrogen bonding, generated by AOH, C@O, and CAOAC groups. The free and associated groups provide the equilibrium in these polymer blends via hydrogen bonds; (b) Quantitative measurements of weight loss from TG/DTG plots show that CAP is less thermally stable than the HPC and CAP/HPC blends, as the anhydroglucose units increase the rigidity of the HPC chain.…”
Section: Resultsmentioning
confidence: 95%
“…A previous article, 23 has shown that the specific interactions in a blend, including hydrogen bonding, ion-ion pairing, and electron-donor and electron-acceptor complexation, etc., produce a favorable mixing enthalpy and hence may lead to miscibility among components. The presence of a solvent in the blend system introduces the polymers-solvent interactions as a function of polymers composition, concentration of polymers solution and temperature, and determines different conformations.…”
Section: Surface Tension Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect may be explained if one considers the formation of hydrogen bonds between HPC and glucose, a phenomenon widely observed for sugars. [10,23] When both S1 and S2 are irradiated, the surface polarity of the samples increased with augmentation of the UV Table 3. The surface tension components and interfacial tension with water (in mN/m) of HPC/glucose films before and after UV exposure at different periods of time t UV (in minutes).…”
Section: Surface Wettability and Interfacial Energymentioning
confidence: 96%
“…[9] The reasons for its widespread acceptance include (1) great solubility characteristics in gastrointestinal and other organic fluids, (2) non-interference with tablet disintegration and drug availability, (3) flexibility, chip resistance and absence of taste and odor, (4) stability in the presence of heat, light, air or reasonable levels of moisture, and (5) ability to incorporate color and other additives into the film or tablet without difficulty. The HPC good solubility in most polar organic solvents makes it possible to prepare stable aqueous and nonaqueous solutions [10] thus forming thermotropic as well as lyotropic liquid crystalline phases in many solvents [11] . HPC exhibits the appropriate attributes of an ideal polymer for film coating, as required in release oral delivery.…”
Section: Introductionmentioning
confidence: 99%